2000
DOI: 10.1176/appi.ajp.157.9.1453
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Differences Between First-Admission Schizophrenia and Psychotic Affective Disorders

Abstract: Even early in its course, schizophrenia is distinguishable from psychotic affective disorders by global and specific neuropsychological deficits. These deficits might contribute to the disability and poor outcome associated with schizophrenia in the mid- and long-term course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 44 publications
12
75
0
5
Order By: Relevance
“…In contrast, Hobart et al [42] have found a significant difference between both groups on the vocabulary subtest of the WAIS-III (p < 0.005), with a large effect size (d = 0.97), making this variable one of the most discriminating of all the variables studied. A similar result was found in patients experiencing their first psychotic episode, with bipolar patients being less impaired than schizophrenic patients on the vocabulary subtest of the WAIS-R [54]. …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In contrast, Hobart et al [42] have found a significant difference between both groups on the vocabulary subtest of the WAIS-III (p < 0.005), with a large effect size (d = 0.97), making this variable one of the most discriminating of all the variables studied. A similar result was found in patients experiencing their first psychotic episode, with bipolar patients being less impaired than schizophrenic patients on the vocabulary subtest of the WAIS-R [54]. …”
Section: Resultssupporting
confidence: 67%
“…Ten studies have compared bipolar and schizophrenic patients while performing this test [42, 44, 46,50,51,52, 54, 65, 69, 70]. Six studies did not find any difference between the two groups [44, 46, 50, 51, 69, 70].…”
Section: Resultsmentioning
confidence: 99%
“…Both groups were compared with respect to executive functioning. Similar levels of cognitive impairment would be expected in mania and acute schizophrenia, since some overlapping has also been observed with respect to clinical symptomatology or neuroimaging findings in these states [4, 19, 24, 25], in spite of contradictions of several investigations [26, 27]. Nevertheless, less attention has been paid to the most extreme positions of the postulated common pathway between schizophrenia and bipolar disorder, such as remitted bipolar patients and negative schizophrenics.…”
Section: Methodsmentioning
confidence: 91%
“…To date, only a few studies compared the cognitive functioning of these groups, and they have not provided any evidence for between-group cognitive differences. 19,62 The current study does not provide any information regarding longitudinal progression of cognitive deficits from early to chronic phases of illness. Only 6 of the studies included in the meta-analysis investigated cognitive impairment in FE patients with AP.…”
Section: Discussionmentioning
confidence: 99%